Dalbavancin as an alternative to traditional outpatient parenteral antimicrobial therapy for deep gram-positive infections – an observational, retrospective review - Hongkai Bao; Rita Igwilo-Alaneme; Fnu Sonia; Kelsie Cowman; Mani Kahn; Priya Nori (Therapeutic Advances in Infectious Disease, 2024)
Background: Treatment of invasive gram-positive infections in complex patient populations is challenging. Dalbavancin, approved for skin and soft tissue infections, offers advantages in this setting due to its long half-life and infrequent dosing. However, less is known about the outcomes of off-label dalbavancin for deeper infections. Objectives: The objective of this study is to examine the feasibility and outcomes of patients with complex gram-positive infections treated with dalbavancin as an alternative to standard outpatient parenteral antimicrobial therapy (OPAT). Methods: We conducted a multicenter, retrospective review of adult patients managed within an OPAT program with intravenous dalbavancin for off-label indications. Adult patients were included if they had treatment details and follow-up documented between January 2020 and June 2023. Details of dalbavancin use including indications for prescription were captured. Outcomes of interest included 90-day infection recurrence, prosthesis retention rates, 90-day mortality, and adverse medication events. Results: In all, 61 patients received dalbavancin, mostly as sequential therapy. Twenty-three percent received dalbavancin strictly in the outpatient setting. Dalbavancin was used primarily for hardware (fracture, spine, or joint), native bone or joint, and complicated soft tissue infections. The predominant pathogen was Staphylococcus aureus (61%). Dalbavancin was frequently prescribed as a two-dose 1500 mg regimen (49%) due to persistent infection (23%), difficult line access (30%), difficulty achieving therapeutic vancomycin levels (18%), or substance abuse history (18%). Overall, six patients (10%) had infection recurrence and no patients died during the follow-up period. Three of eight patients with hardware retention had infection recurrence. Adverse effects were minimal and mostly self-limiting. Conclusion: Dalbavancin is an efficacious and safe alternative to standard OPAT, especially in those with barriers to traditional long-term intravenous antibiotics. Improved outcomes may be achieved with hardware removal. Dalbavancin may facilitate early discharge or prevent hospitalizations. Comparative studies of standard OPAT regimens versus dalbavancin are needed.